Assessing the Impact of Mobile Technology on Fintech Enabled Payment Systems in Emerging Markets - Mursalim Nohong; Nur Alamzah; Amer Ahmad Hatamleh; Muhammad Try Dharsana; Andi Iqra Pradipta Natsir; Fakhrul Indra Hermansyah (International Journal of Interactive Mobile Technologies (iJIM), 2026)
This study examines the influence of competitive innovation and ecosystem integration on customer loyalty and usage intensity within Indonesia’s highly competitive mobile payment sector, focusing on the three leading providers: OVO, GoPay and DANA. A cross-sectional survey of 395 active users and analysis using partial least squares structural equation modelling (PLS-SEM) reveal that lifestyle embeddedness fully mediates the effects of both competitive innovation and ecosystem integration on customer loyalty. Both factors significantly enhance lifestyle embeddedness, which in turn strongly predicts loyalty and usage intensity. These findings shift the theoretical perspective from feature-based competition to the behavioural embedding of services into daily routines. For practitioners, the results highlight that long-term user retention in emerging-market FinTech is primarily achieved through seamless and pervasive ecosystem integration rather than isolated feature superiority. This study is the first to empirically identify lifestyle embeddedness as the central mediating mechanism in a saturated, triopoly-dominated mobile payment market.